Pengaruh Jenis Kelamin, Masa Kerja, Lama Menjabat, Dan Tingkat Pendidikan Terhadap Gaya Kepemimpinan Kepala Ruang Laboratorium Klinik - Anwar, Moch; Chalimah, Chalimah (LPPM Universitas Pekalongan, 2024)
Leaders have an important role in determine the success or failure of an organization in achieving its goals. Individual characteristics often influence one's leadership style. The aim of this research is to determine the influence of gender, work period, length of service and educational status on the leadership style applied by the Head of a laboratory unit in a Central Java hospital. The samples obtained were 44 respondents from 130 heads of laboratory units at Central Java Regional Hospital. This research is a correlational quantitative research with a cross sectional approach. The analytical tests used include data normality test, multicollinearity test, autocorrelation test, and multiple logistic regression analysis. The research results show that partially, only the work period variable has a significant effect on leadership style with a p value of 0.014 < alpha 0.05. The results of this research have the implication that when selecting leaders you can consider the individual's work period or seniority. It is hoped that future research can increase the number of respondents and examine other variables that have not been studied, such as participation in leadership training and the personality type of heads of hospital laboratory units in Central Java.